Itaconate, Arginine, and Gamma-Aminobutyric Acid: A Host Metabolite Triad Protective Against Mycobacterial Infection - Kim, Jin Kyung; Park, Eun-Jin; Jo, Eun-Kyeong (Frontiers in Immunology, 2022)
Immune metabolic regulation shapes the host-pathogen interaction during infection with Mycobacterium tuberculosis (Mtb), the pathogen of human tuberculosis. Several immunometabolites generated by metabolic remodeling in macrophages are implicated in innate immune protection against Mtb infection by fine-tuning defensive pathways. Itaconate, produced by the mitochondrial enzyme IRG1, has antimicrobial and anti-inflammatory effects, restricting intracellular mycobacterial growth. L-arginine, a component of the urea cycle, is critical for the synthesis of nitric oxide (NO) and is implicated in M1-mediated antimycobacterial responses in myeloid cells. L-citrulline, a by-product of NO production, contributes to host defense and generates L-arginine in myeloid cells. In arginase 1-expressing cells, L-arginine can be converted into ornithine, a polyamine precursor enhances autophagy and antimicrobial protection against Mtb in Kupffer cells. Gamma-aminobutyric acid (GABA), a metabolite and neurotransmitter, activate autophagy to induce antimycobacterial host defenses. This review discusses the interplay among the three metabolites in host protection against mycobacterial infection. Understanding the mechanisms by which these metabolites promote host defense will facilitate the development of novel host-directed therapeutics against Mtb and drug-resistant bacteria.